PENGEMBANGAN TENAGA KEPENDIDIKAN - Anas Harun (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2013)
To achieve the success of education, teachers should be the human resources (HR) which the development is main priorities. Hard competiton increasingly nowadays requires tenacity, patience, the ability to anticipate, speed and accuracy to think and act in order to remain a role. Education personnel are those who meet the requirements specified in the legislation in force, appointed by the competent authority and entrusted with the task of other countries, defined by something the legislation in force. The development of educational staff can be done with a path or way of training and track non-training, track training such as continuing education, upgrading, seminars, workshops, etc., track non training for example can be in the form of promotions, bonuses and incentives, reprimands and punishment.